Poder de mercado, escala e a produtividade da indústria brasileira entre 1994 e 2007 - Clezar, Rômulo Viana (Universidade do Vale do Rio do Sinos, 2010)
This work focuses on the time path of productivity in the Brazilian manufacturing sector and its behavior in the face of structural shocks during the period 1994 to 2007. It presents a model that is capable of estimating the market power and scale effects in order to measure the total factor productivity under imperfect competition. The analysis for the entire industry indicates a high degree of market power by 1999 and a significant increase in it after the change of the exchange rate regime. Also, for the entire industry, decreasing returns to scale are identified between 1996 and 1998, followed by increasing returns from 1999 to 2002 and, again diminishing returns between 2003 and 2007. However, it was not possible to identify sectors in which the structural shocks were significant. The productivity showed high growth rates in 1999 and negative rates after 2003.
Keywords: escala; markup; produtividade; scale; productivity; Ciências Sociais Aplicadas